Μοριακές προσομοιώσεις οργανικών ηλεκτρονικών υλικών υποκατεστημένου πολυ-θειοφαινίου - Παπασημακόπουλος, Βασίλειος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών. Τομέας Επιστήμης και Τεχνικής των Υλικών (ΙΙΙ). Εργαστήριο Επιστήμης και Τεχνικής των Υλικών, 2018)
Poly (3-hexylthiophene) (P3HT) is one of the most studied semiconducting polymers, because of its enhanced charge carrier mobility and commercial availability. P3HT molecules create stacks that are organized in lamellae, with the hexyl side chains contributing positively to this phenomenon by remaining in a non-interdigitated state. The charge transport in P3HT is accomplished through positively charged carriers of polaronic nature. Also, P3HT does not retain one form in the bulk: polymorphism is identified in both the crystalline and amorphous regions, which is verified both by experimental and computational works. In the present diploma thesis the crystalline polymorph BDα is examined via Molecular Dynamics simulations, using the open-source package LAMMPS, aiming at the determination of structural properties at different temperature conditions. This is accomplished by using trajectories acquired from LAMMPS by means of a benchmarked force field from the literature. It is of high significance that the trajectories have reached thermodynamic equilibrium, so it is checked whether or not this condition is met. Finally the statistically significant parts of the trajectories are collected, in order to calculate structural properties such as intermolecular and intramolecular radial distribution functions and proper dihedral angle populations characterizing the molecular structure.